Regional Shift in the Peak Time of Maximum Indian Summer Monsoon Rainfall in Recent Decades - Kandula V. Subrahmanyam; Prashant Kumar; Narendra Reddy Nelli; Sampelli Anoop; M. V. Ramana; M. Rajeevan; Prakash Chauhan (Geophysical Research Letters)
Abstract Global warming is causing more extreme precipitation events and variability in rainfall patterns, which are affecting the timing of peak rainfall occurrence and impacting the hydrological cycle in evolving climates. This study examines spatial rainfall trends across India during the Indian Summer Monsoon period from 2001 to 2020, utilizing GSMaP_ISRO data. Analysis reveals a significant rise of 2 mm/day in rainfall over west central India from 2011 to 2020. Additionally, an investigation into the timing of peak rainfall demonstrates an early (late) peak over the Indo‐Gangetic Plain (central India) in recent years, likely influenced by changes in aerosol loading. The present results suggest a significant shift in rainfall peak time with potential implications for agriculture, hydrology, and disaster management.